Uncovering the hidden costs of offshoring: The interplay of complexity, organizational design, and experience. (22nd September 2012) - Larsen, Marcus M.; Manning, Stephan; Pedersen, Torben
Abstract This study investigates estimation errors due to hidden costs—the costs of implementation that are neglected in strategic decision‐making processes—in the context of services offshoring. Based on data from the Offshoring Research Network, we find that decision makers are more likely to make cost‐estimation errors given increasing configuration and task complexity in captive offshoring and offshore outsourcing, respectively. Moreover, we show that experience and a strong orientation toward organizational design in the offshoring strategy reduce the cost‐estimation errors that follow from complexity. Our findings contribute to research on the effectiveness of sourcing and global strategies by stressing the importance of organizational design and experience in dealing with increasing complexity. Copyright © 2012 John Wiley & Sons, Ltd.